Does Government Spending Crowd In Private Consumption? : Theory and Empirical Evidence for the Euro Area - Coenen, Gunter (IMF Working Papers; Working Paper ;, 2005)
In this paper, we revisit the effects of government spending shocks on private consumption within an estimated New-Keynesian DSGE model of the euro area featuring non-Ricardian households. Employing Bayesian inference methods, we show that the presence of non- Ricardian households is in general conducive to raising the level of consumption in response to government spending shocks when compared with the benchmark specification without non-Ricardian households. However, we find that there is only a fairly small chance that government spending shocks crowd in consumption, mainly because the estimated share of non-Ricardian households is relatively low, but also because of the large negative wealth effect induced by the highly persistent nature of government spending shocks.